Critical Evaluation of Impedance Phlebography for the Diagnosis of Deep Vein Thrombosis - Wu, Kenneth K; Hoak, John C; Barnes, Robert W; Frankel, Stuart L (Thrombosis and Haemostasis, 1974)
In order to evaluate its daily variability and reliability, impedance phlebography was performed daily or on alternate days on 61 patients with deep vein thrombosis, of whom 47 also had 125I-fibrinogen uptake tests and 22 had radiographic venography. The results showed that impedance phlebography was highly variable and poorly reliable. False positive results were noted in 8 limbs (18%) and false negative results in 3 limbs (7%). Despite its being simple, rapid and noninvasive, its clinical usefulness is doubtful when performed according to the original method.